Contributions of the French Strategic Environmental Assessment to Brazilian planning in water source areas: the Billings Reservoir sub-basin case - Duarte, Carla Grigoletto; Souza, Larissa Ribeiro; Santos, Simone Mendonça dos (Sustainability in Debate, 2022)
Strategic Environmental Assessment (SEA) is a tool that aims to integrate environmental issues into decision-making processes, usually to support the development of sectoral or territorial plans and programs. SEA is mandatory in the European Union and is applied to water management in France. Water management in Brazil is inspired by the French model, but does not have SEA; in the state of São Paulo watersheds of interest for public supply have specific norms and can count on a Development and Environmental Protection Plan (PDPA). In this research we explore three potential contributions of SEA as adopted in French water management for the case of the PDPA of the Billings Reservoir sub-basin. We conducted an evaluative case study for this PDPA, a literature review on French practices, and comparative analysis. We conclude by indicating potential contributions of SEA for the definition of objectives, scoping, and study of alternatives of the PDPA-Billings.